Students Motivation and Preferences in Choosing STAB Negeri Raden Wijaya - Sadtyadi, Hesti (International Journal of Multidisciplinary Sciences, 2025)
This study aims to identify the key factors influencing students' choice to enroll at STAB Negeri Raden Wijaya, a state Buddhist higher education institution in Indonesia, and examine the effectiveness of its online media as promotional tools. Despite showing positive enrollment growth, understanding what attracts students to choose this institution becomes crucial for strategic development. Using a mixed-method approach with explanatory sequential design, the study combined quantitative surveys (n=150) and qualitative interviews (n=15) to gain comprehensive insights. The quantitative phase identified factors through factor analysis, while the qualitative phase provided deeper understanding through semi-structured interviews with prospective students and stakeholders. Results revealed four primary factors influencing student choice: (1) academic quality and institutional reputation, accounting for 32.5% of variance, encompassing teaching quality and program offerings; (2) environmental and family cultural factors (24.3%), including Buddhist family background and community support; (3) campus facilities and environment (18.7%), covering infrastructure and learning resources; and (4) institutional reputation (15.2%), relating to graduate employability and alumni success. Analysis of online media effectiveness showed limited engagement despite growing enrollment, with only 4-8% impact from social media and 1% from website on student recruitment, primarily due to static content and lack of interactive features. The study concludes that STAB Negeri Raden Wijaya's growth is primarily driven by academic quality and cultural factors, while suggesting the need for enhanced digital presence to better support student recruitment efforts.